Linguistic responses according to Abdul Hamid Al-Farahi: his responses in grammatical methods as an example - Salem, Hussein; Yahya, Kiyan (Al-Adab Journal, 2025)
This research is concerned with the efforts of a non-Arab scholar of Arabic who has given their evidence in the language of the best books of God. It is a research devoted to Al-Farahi’s responses regarding grammatical methods, clarifying the audacity of a foreigner of non-Arab origin to criticize many of the decisions of Arab lexicographers morphologists and grammarians are both early and late alike. He made his statement with great linguistic power and mastery. In this research, I detailed  his responses on methods from his responses on grammatical issues, because the methods to which cited Al-Farahi’s responses were not allocated to independent sections in the well-known ancient grammar works, as were the issues of grammar.I decided to start with the theme of submitting and delay, because it does not involve a shortage or an increase, but rather it includes all the elements of composition, but with an advance and a delay in them, then I took  the axis of deletion and addition; Because his examples are surrounded by deficiency or addition and do not remain in their original state, then I concluded with the axis of the oath ; Because it is a method that can only be constructive, while the examples of the first two axes can be declarative or can be composed , and that was the case  It was presented in a way that can only be composed.